معيقات تطبيق التخطيط الاقتصادي واثرها على التنمية الاقتصادية: درسة حالة السودان خلال الفترة من ( 1946 م - 2016 م ) من وجهة نظر خبراء الاقتصاد والعمل الإداري والتخطيطي في السودان) - د. صلاح محمد ابراهيم احمد,; محمد مسعود محمد الدريس, (White Nile Journal for Studies and Research, 2017)
The study has dealt with the components of the economic planning and its impact on economic development-case study on during the period from (1947-2016). The study also aims at identifying the impact of economic financial and physical conditions in Sudan on the success of economic planning, as well as the impact of political and security factors on application of sound economy, knowing the role of administrative leadership and its influence in implementation of economic development plans and programs. The study used the descriptive, statistical analytical approach The study found the following results:- The lack of optimal use of economic resources has led to deviation of plans. because development plans are not made on the basis of available resources. The instability of politics and security leads to fragility of infrastructure and impedes the implementation of development projects due to social instability, civil wars and tribal conflicts. The weakness of the leaders in administrative planning and bureaucratic procedures, due to poor training. Lack of rehabilitation, professional and scientific specialization leads to the lack of coordination between the economic sectors; which affect the planning process and waste the resources. The study recommended the followings: The state should take care by enumerating the material and human resources that are needed to be used optimally It shall also pay attention to training and rehabilitation of senior planning and executive leaders as well as putting the right person in the right place, according to scientific and professional discipline. It should also provide security and peace to contribute to community stability and cessation of wars and tribal conflicts.